Chest computed tomography (CT) features in children with reverse transcription‐polymerase chain reaction (RT‐PCR)‐confirmed COVID‐19: A systematic review. Issue 5 (30th September 2020) - Simoni, Paolo; Bazzocchi, Alberto; Boitsios, Grammatina; De Leucio, Alessandro; Preziosi, Marco; Aparisi Gómez, Maria Pilar
Summary: To describe the chest CT features reported in children with confirmed COVID‐19 infection, published in English literature. A systematic review was completed on PubMed, Embase and Scopus databases on the 1st of June 2020 using the PICO strategy. The NIH Quality Assessment Tool was used to assess the quality of the selected articles. The systematic review was evaluated by Case Series Studies and the Preferred Reporting Items for a Systematic Review and Meta‐analysis of Diagnostic Test Accuracy Studies (PRISMA). The extracted data were assessed and compared with those reported in the adult population. Seventy‐two articles were retrieved from the database search and screened by the title, abstract and keywords. Eleven articles were deemed eligible for full‐text assessment. Nine articles were included for the data extraction and in the final analysis. Chest CT features in children with COVID‐19 differ from those in adults. 'Ground‐grass opacities' (GGOs) are the most commonly described abnormalities, but closely followed by a combination of GGO and consolidation, not usual in adults. Children tend to have a more variable involvement than the subpleural and posterior and basal topography described in adults. Interlobular thickening and air bronchogram found in adults with COVID‐19 are not frequent in children. Pulmonary embolism reported in up to 30% of adults has not been yet reported in children. Original articles describing chest CT features in children with COVID‐19 in the English literature are limited to small populations of Chinese children. Chest CT imaging features are very diverse across the selected studies and globally different from those reported in adults. Data from children of different countries would provide a more comprehensive description of chest CT features in children with COVID‐19.